2(w+1)+4w=3(2w-1)+8

Simple and best practice solution for 2(w+1)+4w=3(2w-1)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(w+1)+4w=3(2w-1)+8 equation:


Simplifying
2(w + 1) + 4w = 3(2w + -1) + 8

Reorder the terms:
2(1 + w) + 4w = 3(2w + -1) + 8
(1 * 2 + w * 2) + 4w = 3(2w + -1) + 8
(2 + 2w) + 4w = 3(2w + -1) + 8

Combine like terms: 2w + 4w = 6w
2 + 6w = 3(2w + -1) + 8

Reorder the terms:
2 + 6w = 3(-1 + 2w) + 8
2 + 6w = (-1 * 3 + 2w * 3) + 8
2 + 6w = (-3 + 6w) + 8

Reorder the terms:
2 + 6w = -3 + 8 + 6w

Combine like terms: -3 + 8 = 5
2 + 6w = 5 + 6w

Add '-6w' to each side of the equation.
2 + 6w + -6w = 5 + 6w + -6w

Combine like terms: 6w + -6w = 0
2 + 0 = 5 + 6w + -6w
2 = 5 + 6w + -6w

Combine like terms: 6w + -6w = 0
2 = 5 + 0
2 = 5

Solving
2 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4(v+2)+2=2(v+6) | | 5x^2=13x-12 | | 45=3x | | 60=3x+15 | | -5(a-3)=-8(a+6) | | 3x-8*17=36x | | 3x-87-7x=39+8x+6 | | -k+9+2k-6=51 | | 9y^2-30y+25=0 | | 3x-4+4=66 | | ln(7x-3)= | | ln(7x-3)=52 | | (x+2.8)(x+1.3)=0 | | 15(x^2)=0 | | 3x^4-8x^2-16=0 | | (8-5)n=43 | | -2=11+9x-15-7x | | 4k+3-3k+2=-18 | | 8+5-n=27 | | 18z-10=16z+8 | | -1.4x+3.5=0.6x+0.9 | | 0.67x-2=0.2x-0.6 | | 0.667x-2=0.2x-0.6 | | 0.4x-0.25=0.5x+0.75 | | -3-8*x=21 | | 10a+5=5a+15 | | -3x+8=2(x-11) | | 0.75x-0.3333=0.666667x-0.75 | | -0.333333x+0.75=0.25x+0.166667 | | y=-4.828427125 | | 3x+5-2x=-28 | | -0.5x+1.5=2x-5 |

Equations solver categories